2007
DOI: 10.1007/s11265-007-0129-7
|View full text |Cite
|
Sign up to set email alerts
|

Trend and Challenge on System-on-a-Chip Designs

Abstract: The success of system-on-a-chip (SoC) hinges upon a well-concerted integrated approach from multiple disciplines, such as device, design, and application. From the device perspective, rapidly improving VLSI technology allows the integration of billions of transistors on a single chip, thus permitting a wide range of functions to be combined on one chip. From the application perspective, numerous killer applications have been identified, which can make full use of the aforementioned functionalities provided by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…When we can't put more component in SoC, its computational power and efficiency will not be increased. As applications require more Computational power in the next few years, it is clear that we need multiple processors, processing elements, and function units [7]. Also the pace at which the transistors and ICs are scale down, the wire delays doesn't.…”
Section: Network-on-chipmentioning
confidence: 99%
“…When we can't put more component in SoC, its computational power and efficiency will not be increased. As applications require more Computational power in the next few years, it is clear that we need multiple processors, processing elements, and function units [7]. Also the pace at which the transistors and ICs are scale down, the wire delays doesn't.…”
Section: Network-on-chipmentioning
confidence: 99%
“…On regression, it is found that the emf observed in mV, found best fit for polynomial expression of the order three is found best fitted. Then these three equations are averaged to derive the final calibrated equation as DO in % = 2E-05(V DO ) 3 …”
Section: B Calibration Of Soc To Do In Percentagementioning
confidence: 99%
“…Recent trends in System-on-a-Chip (SoC) show that an increasing number of special-purpose processors in these systems are added to improve the efficiency of frequently-used operations [5]. For example, NVIDIA offers a CUDA-compatible mobile processor [10] to support demanding operations on mobile platforms.…”
Section: Introductionmentioning
confidence: 99%